(untitled) (Research, Society and Development, 2020)
The present study aimed at evaluating the different storage periods of eggs from free-range hens on incubation variables. Treatments were composed according to the following egg storage periods: 1 to 5 days, 6 to 10 days, 11 to 15 days and 16 to 20 days. The variables analyzed were egg weight loss, embryonic mortality, hatchability rate and chick weight at birth. The experimental design was completely randomized. The variables related to weight were subjected to analysis of variance and the Scott-Knott test at 5% probability. Egg weight and chick weight at birth were not influenced by egg storage time; however, egg weight loss during storage was greater (P <0.05) from 11 days of storage. Egg weight loss during incubation was greater (P <0.05) in the storage period from 1 to 5 days. The embryonic mortality rate reached 52% in the period from 15 to 20 days, while the hatchability rate decreased in this period, reaching 47.6%. Storage for periods over 16 days should be avoided, as there is a marked reduction in hatchability rate.